The Marriage and Family Therapy Practice Research Network: Current Findings and a Call for Collaboration - Johnson, Lee N.; Anderson, Shayne R.; Wagner, Kaelie N. (European Journal of Mental Health, 2025)
Introduction: Mental health problems continue to rise throughout the world while access to care remains problematic due to low affordability and limited therapist availability. With the mental health crisis only getting worse, clinicians and researchers must work together to improve client outcomes. The Marriage and Family Therapy Practice Research Network (MFT-PRN) was established to improve client care and foster collaborative research in systemic therapy. This project balances research rigor and clinical flexibility, making it accessible and beneficial for practitioners, clients, and researchers.Areas covered: This paper will address the above issues by discussing how the MFT-PRN brings researchers and clinicians together, through routine outcome monitoring (ROM) and providing assessments that track client progress across sessions, allowing clinicians to create better treatment plans. We will also discuss how the MFT-PRN facilitates researcher collaboration by sharing data collected across diverse settings.Expert opinion: Professional experience and research findings suggest that using the MFT-PRN enhances therapy outcomes, reduces treatment length, and improves couple and family relationships. The MFT-PRN has facilitated research that leads to improved client care in areas such as therapeutic alliance, teletherapy efficacy, and the impact of adverse childhood experiences on anxiety.Conclusion: By bringing practitioners and researchers together, the MFTPRN contributes significantly to advancing marriage and family therapy.